Pemberian cookies tepung daun dan biji kelor terhadap berat badan dan status gizi anak balita di wilayah kerja Puskesmas Tampa Padang - Zaki Irwan; Andi Salim; Adriyani Adam (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
Handling of nutritional problems of children under five can be done through the development of food products in the form of Moringa leaf flour cookies and Moringa seed flour cookies given to toddlers, and then assessed an increase in body weight and nutritional status. The purpose of the study was to look at differences in body weight and nutritional status after intervention from Moringa leaf flour cookies and Moringa seed flour cookies in toddlers. The study design uses a Randomized Controlled Trial Single Blind Pre-post Study. The study was conducted in the working area of the Tampa Padang Public Health Center in August-October 2019 on children aged 3-5 years. The number of samples was 50 people, 25 children have interfered with Moringa leaf flour cookies, and 25 children were intervened by Moringa seed flour. Analysis of nutrient consumption of toddler foods using the Nutri Survey program. Maternal nutrition consumption is expressed in percent of RDA. Statistical analysis using the T-test. The results showed changes in body weight before and after giving Moringa seed cookies and Moringa leaf cookies (p=0,025). There is a difference in the increase in weight of the two groups of samples, but statistically has not been able to improve the nutritional status, both those who were given Moringa seed flour substitute cookies and those who were given Moringa leaf flour substitution cookies (p=0,495). In conclusion, there is a change in toddler's body weight, but it is not yet significant to the nutritional status of toddlers. Penanganan masalah gizi anak balita dapat dilakukan melalui pengembangan produk pangan berupa cookies tepung daun kelor dan cookies tepung biji kelor yang diberikan kepada balita, selanjutnya dinilai peningkatan Berat Badan dan Status gizinya. Tujuan penelitian yaitu melihat perbedaan berat badan dan status gizi setelah diintervensi cookies tepung daun kelor dan cookies tepung biji kelor pada anak balita. Desain penelitian menggunakan Randomized Controlled Trial Single Blind Pre-post Study. Penelitian dilakukan di Wilayah Kerja Puskesmas Tampa Padang Kecamatan Kaluku, Kabupaten Mamuju Sulawesi Barat. Waktu penelitian dimulai pada bulan Agustus – Oktober 2019 terhadap anak balita berumur 3-5 tahun. Jumlah sampel 50 orang, 25 anak diintervensi cookies tepung daun kelor dan 25 anak diintervensi tepung biji kelor. Analisis zat gizi konsumsi pangan anak balita menggunakan program Nutri Survei. Konsumsi gizi ibu dinyatakan dalam persen AKG. Analisis statistik menggunakan uji T. Hasil penelitian menunjukkan perubahan berat badan sebelum dan setelah pemberian cookies biji kelor dan cookies daun kelor dengan nilai p=0,025 (p-value<0,05). Terdapat perbedaan peningkatan BB kedua kelompok sampel, namun secara statistik belum bisa memperbaiki status gizi, baik yang diberi cookies subtitusi tepung biji kelor maupun yang diberi cookies subtitusi tepung daun kelor dengan nilai p=0,495 (p-value>0,05). Kesimpulan, terdapat perubahan berat badan balita namun belum signifikan terhadap status gizi balita yang mendapatkan cookies berbahan daun kelor.